Factors Affecting Pregnancy Depression as A Risk Detection for Postpartum Depression - Nina Zuhana; Suparni (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Antepartum depression frequently precedes postpartum depression. Postpartum depression entails a direct impact on the laboring mother and is a long-term risk to the mother's mental health, therefore it is essential to screen and detect the risk of postpartum depression since pregnancy. This study aimed to analyze the factors influencing pregnancy depression descriptively in the Pekalongan Regency Health Office. This research is a quantitative descriptive study using a cross-sectional approach. The population in this study were pregnant women in the Community Health Center in the working area of the Pekalongan Regency Health Office. The sampling technique used is proportional random sampling. The collection of data on the characteristics of pregnant women used a demographic questionnaire, while depression experienced by pregnant women used the EPDS (Edinburg Prenatal Depression Scale) questionnaire. The results of the study showed that most respondents (75.9%) did not experience pregnancy depression, however, 24.1% experienced pregnancy depression, and those who experienced pregnancy depression occurred among pregnant women of reproductive age, with secondary education or above, unemployed respondents, multigravida pregnancies, have never experienced an abortion, and some respondents were depressed by unwanted and unplanned pregnancies, as well as were not supported by their spouses. Thus, special services for pregnancy as an effort to prevent and take action for screening/early detection of signs of pregnancy depression are required and necessary to be procured.